Programming and Reprogramming Artworks: A Case of Painting and Practicing Conceptual and Media Art by Other Means - Tomas, David (Intermédialités / Intermediality, 2009)
Programming and Reprogramming Artworks discusses the “needlegraph” practice of Rosika Desnoyers, its relationship to the concept of programming and the automation of manual labor. The paper explores the artist’s engagement with a history of errors that is mapped against the automated programme that is inherent in the production of Berlin work needlepoints and it concludes with an extended discussion of the artist’s practice in relation to conceptual art and an extended or expanded practice of “painting by other means.”